How technologial potentials are undermined by economic and behavioural responses: The treatment effect of endogenous energy efficiency measures - Helena Meier; Christian Tode (Institute of Energy Economics at the University of Cologne (EWI), 2015)
Governments worldwide spend increasing amounts of money on policy schemes to reduce energy consumption and related carbon emissions. We investigate the actual treatment effect of energy efficiency measures and therein compare actual demand responses to technological potentials. Based on a demand system analysis of household data and by approximating unobserved energy awareness, we find economic and behavioural responses that counteract expected savings from energy efficiency. Results show strong rebound and even backfiring effects but also suggest heterogeneity of the effectiveness driven by behavioural concepts, such as sunk cost fallacy or habit formation. Understanding these can contribute to target-oriented policy designs and increased effectiveness and efficiency of policies.
Keywords: C21; D12; Q58; 330; policy evaluation; household demand; unobserved heterogeneity; energy efficiency